Método canguru: (des) atenção ao binômio mãe-bebê na estratégia saúde da família - Batista, Tarsila Nery Lima (2017)
Introduction: In recent years, the Ministry of Health has been carrying out actions to contain the fragmentation of care provided to pregnant women and newborn babies and reduce the neonatal morbidity and mortality in Brazil. The Kangaroo Mother Method was incorporated as a health policy for improving care to the newborn premature, with active participation of Primary Health Care. Objective: To analyze the maternal care with the newborn in the third step of the Kangaroo Mother Method and the assistance given by professionals of the Family Health Strategy to the mother-baby kangaroo. Method: This is a qualitative research, descriptive-exploratory, submitted to the Research Ethics Committee at the Lauro Wanderley University Hospital, getting opinion 1,515,237 CAAE 54391316.7.0000.5183.The participants were 10 mothers of newborn infants whose parturition was performed in one of the maternities entered the study. The data were collected by means of interviews, in the months of May and June of 2016, analyzed from the content analysis technique proposed by Bardin. Had as its backdrop the obstetrical clinic of a university hospital and a public maternity hospital that meet the preterm and/or low birth weight babies, in addition to Family Health Units in the city of João Pessoa, PB. Results: The reports of mothers-kangaroo show feelings like fear, insecurity and tiredness, to take care of the child in the household; experienced lack of family support and professionals for continuity of method, resulting in weakness of the assistance to the mother-baby at this stage of the kangaroo mother method. Conclusion: To continue to provide care to the mother-baby kangaroo, it is necessary to train professionals in the Family Health Strategy in relation to the method, strengthen the bond of family healthcare team with the community, establish a home visit to this dual, in the routine of teams, and propitiate the comprehensiveness of care.